PERBEDAAN HASIL BELAJAR PERBEDAAN HASIL BELAJAR SISWA YANG DIAJAR MENGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN PROBLEM BASED LEARNING PADA MATERI POKOK PENCEMARAN LINGKUNGAN KELAS X IPA SMA NEGERI 1 SUNGGAL - Trioki Ningsih; Puji Prastowo (Universitas Negeri Medan, 2017)
This research aimed to determine the differences between student’s learning outcomes that were taught by used discovery learning and problem based learning models on topic of environmental pollution in grade x SMA Negeri 1 Sunggal in academic year 2014/2015, The population of all of the students at grade X, that consisted of 4 classes and total of the students were 156 students. The samples were taken at random sampling of two classes, with details class X2 used discovery learning model and X1 used problem based learning model and each class numbered 39 students, so the number of samples in this study were 78 students. Type of research was experimental. The results showed that the learning outcomes of students who were taught by using discovery learning model was 82,05 ± 8,25, while the learning outcomes of students who were taught by using the problem based learning model was 76,41 ± 8,15. The result from the t-test at α = 0,05 with th 3,044; tt 1,995; and dk 76 refer that there was significant different from student’s learning outcomes who were taught using discovery learning model with problem based learning model on topic of environmental pollution in grade X SMA Negeri 1 Sunggal in academic year 2014/2015.Keywords : discovery learning, learning model, learning outcomes, problem based learning